Managment in the global economy opportunities and risks - Neterda, Filip (2008)
The thesis start from general introduction to globalization but its focus is on the following areas: global buying of company inputs (sourcing), expanding on the foreign/global markets (output) and managing the risks associated with globalization (increased competition, foreign currency and raw material/inputs hedge). Overall the thesis is practical in its approach and thus it provides the real applicable approaches in terms of the management in the global economy. Despite these practicalities the thesis also aims at analyzing the more general business environment for global activities of a firm. This is realized in section on economic assessment of the market and evaluation of foreign currency fundamentals.